2014
DOI: 10.1002/tox.21951
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of polyphenols from Padina boergesenii against ferric nitrilotriacetate induced renal oxidative damage: With inhibition of oxidative hemolysis and in vitro free radicals

Abstract: The aim of this study was to evaluate the antioxidant activities of diethyl ether (DEE) and methanol (M) extracts from brown alga Padina boergesenii using in vitro and in vivo antioxidant assay, which may help to relate the antioxidant properties with the possible outline of its ameliorative effect. M extract showed higher radical scavenging activity through ferric reducing antioxidant power 139.11 µmol tannic acid equivalent/g; DPPH 71.32 ± 0.56%; deoxyribose radical 88.31 ± 0.47%, and total antioxidant activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Dietary antioxidants have been shown to protect the cells from damage caused by oxidative stress and to fortify the defense system against degenerative diseases (Clarke et al 2008;Riccioni et al 2008). Several natural antioxidants and phytonutrients present in dietary sources reduced the oxidative stress and oxidative stress-induced hemolysis (Tulipani et al 2011(Tulipani et al , 2014Widen et al 2012;Rajamani et al 2014;Phrueksanan et al 2014). …”
Section: Introductionmentioning
confidence: 98%
“…Dietary antioxidants have been shown to protect the cells from damage caused by oxidative stress and to fortify the defense system against degenerative diseases (Clarke et al 2008;Riccioni et al 2008). Several natural antioxidants and phytonutrients present in dietary sources reduced the oxidative stress and oxidative stress-induced hemolysis (Tulipani et al 2011(Tulipani et al , 2014Widen et al 2012;Rajamani et al 2014;Phrueksanan et al 2014). …”
Section: Introductionmentioning
confidence: 98%
“…Cellular and molecular studies have reported that algal products are potential antioxidants suggested to prevent cancer metastasis . We reported in our earlier study about the ameliorative effect of polyphenols and inhibition of oxidative hemolysis being identified in crude extract from this alga . The alga was extracted and partitioned through silica gel with combination of different solvent system such as methanol:ethylacetae (ME) (1:3), chloroform:ethylacetate (1:3), and butanol:ethylacetate (1:3) five fractions (F1‐F5) from each system was collected and screened for in vitro radical scavenging activity (data not shown).…”
Section: Introductionmentioning
confidence: 99%